THE CHALLENGES OF PRE-SERVICE ENGLISH TEACHER AT EDUCATION DEPARTMENT STKIP PGRI BANGKALAN IN IMPLEMENTING TECHNOLOGY DURING INTERNSHIP - Siti Fatimah Zuhroh; Arfiyan Ridwan; Hendra Sudarso (STKIP Persada Khatulistiwa Sintang, 2023)
This study aims to explore the challenges faced by pre-service teachers in implementing technology in their teaching practice and to investigate and overcome challenges during the teaching practicum program. The design of this research is a qualitative research using case study method. The participants of this study were last semester students who did internships in different regions. Data was taken by direct interviews. Data analysis is based on research questions. The findings reveal that understanding technology and implementing technology as a challenge for pre-service teachers.Keywords: Keywords: Challenges of Teaching Practicum, Pre-service Teacher, Qualitative Research.